“Determinación de parámetros tecnológicos la conservación en almíbar de tubérculos de oca (oxalis tuberosa - Reinerio Reiner Nauca Edquen (2015)
This research was carried out in order to establish the appropriate technological parameters for obtaining whole oca in syrup (Oxa/is tuberosa), with optimum sensory and nutritional characteristics. The research included studies of the raw material, the process and the final product, performing as the case, physical characterizations, physicochemical, microbiological and sensory analysis about the study factors proposed. The oca tuber ( Oxalis tuberosa) variety pumpkin oca was from the city of Bambamarca Cajamarca departmento. The characterization of oca tuber was of length ( 100 mm) diameter (27mm ), average weight per unit 63,5g, color light yellow without any physical defects. physicochemical analysis fresh tuber oca reportad a 83, 17% moisture rates, 1,25% protein, 0,38% fat, 1,53 % fiber, 14,47% carbohydrates, ash 0,73%, pH 6,0, Brix 8 and a titratable acidity voiced in oxalic acid 0.088 %. The flow chart for obtaining syrup oca stablished throught the following processes, selection and classification, washing, disinfecting, blanched, peeled, cut, preparation of syrup, packaged, closed, heat treatment, cooled off, cleaning and storage. which the studied factors were; Factor A two types of presentation (A1 = integer Oca, A2 =oca slices), Factor B three types of syrup pH (81 = 2,6 pH, 82 = 2,8 and B3 = 3,0 pH) and Factor C three types of Brix (C1 = 27 ºBrix, C2 = 31 ºBrix y C3 = 35 ºBrix. ). The slowest heating point in the whole Oca in syrup found 4,52 cm from the base of the container to 103 ºC and 5 minutes, 20,38 minutes minimum Po with a CUT =13,8 minutes (overall improved method). The analysis physicochemical of the best selected treatment by sensorial method was T9 (whole Oca, pH 3,8 and 20 º Brix, cooked to 103 ºC x 5 minutes) lt of: 69, 18% moisture, 0.49% protein, O, 12% fat, 0,32% ash, 0,87% fiber, carbohydrates 29,89%, 0,063% titratable aciditv, 122,6 Kcal/100 Q enerQv and a microbioloQical quality harmless.